Multivariate Analysis Illuminates the Effects of Vacuum Drying on the Extractable and Nonextractable Polyphenols Profile of Loquat Fruit. Issue 4 (15th March 2019) - Li, Wenfeng; Wang, Xv; Zhang, Jing; Zhao, Xin; Wu, Yingmei; Tan, Si; Zheng, Qiaoran; Gao, Xiaoxv
Abstract : Abstract: The current study evaluated the effects of vacuum drying on the whole polyphenol profile of loquat fruit, including extractive and nonextractive polyphenols. Absorbance analysis determined that total polyphenol content and antioxidant levels were higher in loquat fruit vacuum dried at 140 °C than in loquat fruit vacuum dried at 70 °C. The results of ultra‐HPLC–triple quadruple mass spectrum analysis showed that 15 phenolic acids and 17 flavonoids were found in dried loquat fruit. Multivariate integrative (MINT) sparse partial least square‐discriminant analysis showed that vacuum drying affects the polyphenol profile of loquat fruit. Co‐analysis of principal component analysis, partial least square‐discriminant analysis, and orthometric partial least square‐discriminant analysis revealed that vacuum drying mainly changed the content of chlorogenic acid, cryptochlorogenic acid, protocatechuic acid, phloretin, and hesperidin in loquat fruit. Chlorogenic acid (12.020 to 39.153 µg/g d.b. [dried base weight]), the main polyphenol in dried loquat fruit, was degraded to caffeic acid (0.028 to 2.365 µg/g d.b.) and protocatechuic acid (0.014 to 18.285 µg/g d.b.) during vacuum drying. Moreover, vacuum drying also induced the isomerization of chlorogenic acid into cryptochlorogenic acid (1.628 to 12.737 µg/g d.b.). These results might be used to develop dried loquat fruit with high levels of polyphenols and antioxidant activity. Practical Application: Interests in polyphenols of loquat fruit had increased greatly because of their possible role in health benefits. This work provided a holistic insight in the effects of vacuum drying on polyphenols profile of loquat fruit. Current results have contributed to the development of vacuum‐drying method, which produced loquat fruit rich in polyphenols. Furthermore, it also suggested that multivariate analysis was a feasible method to reveal the important changes of polyphenols profile during food processing.